The Role of Auditor Independence in Audit Quality and Fraud Mitigation: A Systematic Literature Review - Kekoto Manneh; Indrawati Yuhertiana; Rida Perwita Sari (Jurnal Inovasi Akuntansi (JIA), 2026)
Purpose: This study seeks to investigate the contribution of auditors’ independence to the quality of audit services and the mitigation of financial fraud. It also analyses the contextual, technological, and behavioural factors that influence auditor independence. By integrating perspectives from both developed and emerging economies, the study highlights overlooked issues of independence in digital auditing and gender governance, while suggesting directions for future research and policy development. Method: This study employed a Systematic Literature Review (SLR) guided by the PRISMA framework. The review consisted of 72 peer-reviewed journal articles obtained primarily from the Scopus-indexed database. The selected articles were analysed to identify key themes related to auditor independence, audit quality, fraud prevention, digital tools, and regulatory environments. Findings: The findings identify four main themes: (1) the impact of auditor independence on the credibility of audit reports, (2) the role of independence in fraud detection and prevention, (3) the influence of digital tools on independent audit judgment, and (4) differences in independence practices across regulatory environments. The study concludes that auditor independence enhances professional skepticism and strengthens audit reliability. Implications: This SLR provides implications for audit firms, regulators, and academics. Audit firms need to strengthen safeguards for auditor independence, enhance ethical training, manage non-audit service risks, and reinforce functional independence through stronger governance mechanisms. Regulators should improve oversight and policy frameworks to ensure independence is maintained in both traditional and digital audit environments. For academia, the study identifies research gaps and provides opportunities for future empirical and comparative studies on auditor independence.